Binding fragments of Tractate Temurah and the problem of lishana 'aḥarina - Goldstone, Matthew S., 1985-; Schiffman, Lawrence H.; Hillam, Anne, 1965-; McCann, Laura, 1972-; Taylor, Marvin J.; Engel, Edna. (The Brill Reference Library of Judaism, 2018)
Binding Fragments of Tractate Temurah and the Problem of Lishana 'Aḥarina offers a critical edition of an important Talmud manuscript of tractate Temurah discovered in the library of New York University. Addressing the unique Lishana 'Aḥarina ("alternative version") phenomenon present in this tractate, the present volume suggests a new approach for understanding the editing and transmission of tractate Temurah. This volume also includes a thorough discussion of the conservation and treatment of the manuscript fragments, a codicological and paleographical analysis of the fragments, and a synopsis of the entire first chapter of this tractate. The present work is relevant for study of the redaction and transmission of tractate Temurah and the Babylonian Talmud, as well as for the study of Hebrew binding fragments.